Nondesructive Testing of Composite Materials of Aircraft Elements by Active Thermography - Gordiyenko, E.Yu.; Glushchuk, M.I.; Fomenko, Yu.V.; Shustakova, G.V.; Dzeshulska, I.I.; Ivanko, Yu.F. (Science and Innovation, 2024)
Introduction. Composite materials (CM) are widely used in modern aircraft production. Due to the specificity of CM properties, thermal nondestructive testing (TNDT) is the most promising method for detection of defects in aircraft construction elements made of CMs. Until now, TNDT has not been implemented in the Ukrainian aircraft industry. Problem Statement. To study the dynamics of excess temperature fields on the surface of CM test samples using the active thermography. Purpose. To develop a technique for optimal detection of defects in CM elements and estimation of defect parameters. Materials and Methods. The fiberglass and carbon fiber test samples with the most dangerous and frequent defects at various depths are to be studied. To detect the defects and to determine their parameters, the method of optimal observation of their mage temperature contrast was used after stimulating the samples by thermal pulse of finite duration (0.2-3 s). Results. Experimental dependences of temperature contrast for each defect image as function of observation time have been obtained under various regimes of thermal stimulation and positions of reference (defect-free) area. Requirements for the heat pulse parameters have been elaborated. Algorithms for optimal processing of thermal images sequence have been designed. A protocol of procedure for the TNDT of aircraft CM elements without metallized layers has been developed. Conclusion. 90% defects and depths of their location have been detected using technical means without special requirements to their response time. To detect the remaining 10% defects (in air-filled honeycomb samples and in samples with metallized layers), a thermal stimulation source with a shorter pulse duration and a thermal imager with a higher frame rate are required because of high relaxation rates of the excess temperature fields. The study was supported by the NAS of Ukraine in the framework of research project "Development of Infrared Diagnostic Complex and Procedure for Detecting Defects in Composite Materials of Aircraft Elements and Other Equipment".